2007
DOI: 10.1063/1.2800317
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of critical nucleus during nucleation process of liquid metal sodium

Abstract: To deeply understand the formation mechanism of a critical nucleus during the nucleation process of liquid metal sodium, a system consisting of 10 000 Na atoms has been simulated by using molecular dynamics method. The evolutions of nuclei are traced directly, adopting the cluster-type index method. It is found that the energies of clusters and their geometrical constraints interplay to form the favorable microstructures during the nucleation process. The nucleus can be formed through many different pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…However, the HA bond-type index method is incapable of characterizing atomic cluster structures, especially the larger or nano-clusters. Based on the HA bond-type index, we have proposed a new cluster structure description method of CTIM [15,16] Based on the CTIM, larger clusters combined by different types and numbers of basic clusters can be clearly described. If the central atoms of two basic clusters are neighbors, we define that they belong to the same larger cluster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the HA bond-type index method is incapable of characterizing atomic cluster structures, especially the larger or nano-clusters. Based on the HA bond-type index, we have proposed a new cluster structure description method of CTIM [15,16] Based on the CTIM, larger clusters combined by different types and numbers of basic clusters can be clearly described. If the central atoms of two basic clusters are neighbors, we define that they belong to the same larger cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Then the damped force method [21][22][23] (also called the Gaussian thermostat) is adopted to decrease the temperature of system to 173 K at a cooling rate of 1 Â 10 11 K s À1 . As the crystalline temperature T c is about 243 K at this cooling rate which has determined by our previous work [15], the supercooled temperature scale is in the temperature region of 371-243 K. Then the crystallization of supercooled liquid Na is performed by isothermally running 100 000 time steps (i.e. 500 ps) at 253 K. Finally, the time dependences of the dynamic properties during the isothermal relaxation process are detected by using the time-correlation functions of mean-square displacement (MSD) and non-Gaussian parameter (NGP).…”
Section: Simulation Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…of 1541, 1431 and 1321 bond-types, based on our previous works [7,8,22,23,[33][34][35][36], a new cluster-type index method (CTIM-3) has been proposed. In CTIM-3, a basic cluster can be expressed by nine-integer index of (N, n 1 , n 2 , n 3 , n 4 , n 5 , n 6 , n 7 , n 8 ), where N is the number of nearest-neighbour atoms of the central atom, namely, the coordination number (CN), and n 1 , n 2 , n 3 , n 4 , n 5 , n 6 , n 7 , n 8 in turn denote the numbers of 1441, 1551, 1661, 1421, 1422, 1541, 1431 and 1321bond-types, respectively.…”
Section: Cluster Type Index Methods (Ctim-3) Analysismentioning
confidence: 99%
“…Adopting a new cluster-type index method (CTIM-3) to analyse the local atomic clusters, it is found that the dominant microstructural configurations in the supercooled liquid and amorphous are the icosahedrons and their combinations, especially the intercross-sharing (IS) clusters linked of two icosahedrons (IS-ICO-clusters) can be used to build some larger IS-ICO nanoclusters with different sizes. Highly interesting, in the system the number of atoms in various IS-ICO nano-clusters demonstrates a magic number sequence of 19,23,25,27,29,31,33,35,37,41,43, and so on. The magic number clusters can be classified into three main types: chain-like, triangle-tailed and quadrilateral-tailed.…”
mentioning
confidence: 99%